1998
DOI: 10.1017/s0007114598001822
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of acetylated peptides from the small intestine in sheep and their nutritive value in rats

Abstract: Acetylation is a potential method for protecting dietary peptides from degradation by rumen micro-organisms. As a first step in determining the nutritive value of acetylated peptides, their disappearance in the small intestine of sheep and their ability to support growth in a rat bioassay were measured. 15 N-labelled peptides were prepared from lucerne which had been grown with 15 N-labelled (NH 4 ) 2 SO 4 in the absence of Rhizobium. Peptides were prepared by enzymic hydrolysis of the extracted protein. Two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…The result was similar with that of Wallace et al (1998), who injected acetylated peptides into the duodenum of sheep. It is clear that these in vivo studies suggest a benefi t from acetylation in controlling ruminal breakdown and providing nitrogen to ruminants.…”
Section: Resultssupporting
confidence: 88%
“…The result was similar with that of Wallace et al (1998), who injected acetylated peptides into the duodenum of sheep. It is clear that these in vivo studies suggest a benefi t from acetylation in controlling ruminal breakdown and providing nitrogen to ruminants.…”
Section: Resultssupporting
confidence: 88%
“…As N-Ac-L-Met and N-Ac-L-Val exerted activating effects on the ACY I activity, the APH (treated cells/untreated cells) /ACY I (treated cells/untreated cells) ratio dropped from 1.0 to 0.26-0.34, whereas in the presence of N-Ac-L-Met-L-Ala and N-Ac-L-Ala-L-Ala this ratio increased to 3.7-4.5, so that each type of substrate had specific effects on the corresponding enzyme. The results of the present study therefore show that both aminoacids and N-acetylated peptides are apparently able to cross the hepatocyte plasma membrane as efficiently as their unmodified counterparts, in agreement with previous uptake studies on rabbit (Brachet et al, 1991) and sheep (Wallace et al, 1998) small intestine. There are no procedures available so far to our knowledge for specifically studying the uptake of N-acetylated peptides without any interference from the products of hydrolysis by the liver cells.…”
Section: Dayssupporting
confidence: 93%
“…Deletions of the locus are known to occur in various types of carcinomas including the small cell lung carcinoma and that of renal cells (Naylor et al, 1989;Miller et al, 1989;Erlandsson et al, 1991). Although the uptake of N-acetylated aminoacids and peptides from small intestine has not yet been fully documented (Brachet et al, 1991;Wallace et al, 1998), N-Ac-L-Met has been found to be readily available for protein synthesis in the growing rat (Rostruck and Boggs, 1975;Puigserver et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The same results were found with acetylated pancreatic casein hydrolysate. Under circumstances of restricted feeding in order to eliminate the intake effect, the acetylated hydrolysate retained about half of the nutritive value of unmodified casein hydrolysate 22…”
Section: Resultsmentioning
confidence: 99%
“…It is known that acetylated peptides are absorbed from the small intestine. Moreover, intestinal aminopeptidase N , N ‐acylpeptide hydrolase and acylase I have been found to be responsible for the biological utilisation of N‐acetylated food proteins 19–22. However, until now a detailed assessment of the safety of acetylated faba bean globulin has not been performed.…”
Section: Introductionmentioning
confidence: 99%